Silver-Catalyzed Domino Hydroarylation/Cycloisomerization Reactions of 2-Alkynylquinoline-3-carbaldehydes: Access to (Hetero)arylpyranoquinolines - Bontemps, Alexis; Mariaule, Gaëlle; Desbène-Finck, Stéphanie; Helissey, Philippe; Giorgi-Renault, Sylviane; Michelet, Véronique; Belmont, Philippe (Synthesis, 2016)
A silver trifluoromethanesulfonate catalyzed efficient access to the indolylpyranoquinoline scaffold is reported. Starting from 2-alkynylquinoline-3-carbaldehyde units with various substitution patterns on the quinoline and alkynyl parts, the use of silver trifluoromethanesulfonate (10 mol%) in 1,2-dichloroethane allowed a domino hydroarylation/cycloisomerization reaction, generating (hetero)aryl-functionalized pyranoquinolines. The heteroarenes that were used are N-methylindole (18 compounds, 67–100%), indole, and 2-methylindole (4 compounds, 36–89%), and the reaction was also compatible to a lesser extent with arenes such as pyrroles (5 compounds, 43–90%), 1,3,5-trimethoxybenzene, and 3-methylbenzofuran.
Keywords: Key words; hydroarylation; silver; cycloisomerization; indolylpyranoquinolines; domino reaction; cyclofunctionalization